Role of echocardiography in diagnosing persistent pulmonary hypertension of the newborn (PPHN): A case report - Hasan, Taufiq Hidayat; Anuar, Muhamad Azamin; Kusumawardani, Anisa (2020)
Objective To determine the role of echocardiography in diagnosing PPHN. Case A day one of life baby was suffered from congenital pneumonia requiring nasal CPAP. She was born full term via elective cesarean section with Apgar score 8 and 9. Her birth weight was 3,300 grams. Antenatally, there was history of gestational diabetes mellitus on diet control. She was tachypneic at one hour after delivery. A slight increased opacity on both lungs was found in chest x-ray. There were leucocytosis and increased CRP. Due to worsening respiratory distress, intubation and mechanical ventilation was started. Hypoxemia persisted even though on high setting ventilator with oxygen saturation of 58-70%. Findings on echocardiography were right to left shunt on persistent foramen ovale, dilated right ventricle with tricuspid regurgitation, and pulmonary regurgitation. We administered MgSO4 and sildenafil with inotropes and then patient showed some improvement. We are able to extubate her on day 8 and discharged her on day 16 of treatment. Discussion PPHN remains a challenging problem in neonates. It is often secondary to parenchymal lung disease and mostly seen in term infants. Congenital pneumonia and respiratory distress syndrome cause delayed or impaired relaxation of the pulmonary artery. The diagnosis is based on clinical evidence of labile hypoxemia and confirmed by echocardiography. Conclusion Echocardiography plays an important role in diagnosing PPHN. It should be performed immediately to prevent delay in the diagnosis and management.